IMPLEMENTASI PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA DARMAKRADENAN KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Alivia, Maissy; Kusumaningsih, Oti (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2024)
The Government of Indonesia is committed to achieving the Millennium Development Goals target in the Water Supply and Sanitation sector (WSS-MDG), which is to halve the proportion of the population without access to basic drinking water and sanitation by 2015 (pamsimas.pu.go.id). Kabupaten Banyumas is one of the selected districts to implement the Pamsimas Program. One of the villages in Banyumas Regency selected for the Pamsimas Program is Darmakradenan Village, Ajibarang Sub-district, Banyumas Regency. It is known that during the dry season, the people of Darmakradenan Village experience difficulties in meeting their clean water needs. The results showed that the implementation of the Pamsimas Program in Darmakradenan Village has not been fully successful. This is because there are still several obstacles, such as insufficient human resources and budget resources, unfavorable geographical conditions, lack of communication intensity, and lack of supervision.Based on the conclusions obtained from the research results, the researcher provides the following recommendations: (1) Darmakradenan Village Government needs to improve the quality of human resources implementing the Pamsimas Program through various training or training, (2) Darmakradenan Village Government needs to increase supervision and monitoring of the implementation of the Pamsimas Program, (3) Darmakradenan Village Government needs to increase the intensity and quality of communication and coordination with SPAMS managers, (4) Policy makers need to do careful planning before implementing the Program, namely by thinking about the obstacles that will occur in the future.